Pelayanan Koleksi Karya Cetak Dan Digital Di Unit Penunjang Akademik Perpustakaan Universitas Tadulako - Ahmad Zuhri; Nuraisyah Nuraisyah; Nawawi Natsir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of the research was to determine the implementation of print and digital collection services for users at UPA. Tadulako University Library. In addition, to find out the factors that cause the lack of optimal collection. This research was conducted based on Parasuraman theory about the dimensions of service quality, that is tangibles, reliability, responsiveness, assurance, emphaty. The results of research show that the dimensions of Reliability, Responsiveness, Assurance and empathy have been running well, but the Tangible dimension is still not running optimally, this is due to the number of librarians who have not met the national standards of university libraries and the lack of library promotion activities. The conclusion of this study is that the service of printing and digital collections at UPA Library has not run optimally.